The impact of thermodynamic balancing on the performance of a humidification dehumidification desalination system. (1st March 2021) - Elzayed, Mohamed S.; Ahmed, M.A.M.; Antar, Mohamed A.; Sharqawy, Mostafa H.; Zubair, Syed M.
Highlights: Thermodynamic balancing improves the performance of thermal desalination systems. Experimental investigations are carried out to validate the theoretical model. The experimental results are within ± 6 % of theoretical values. A novel dimensionless enthalpy pinch is introduced to study the performance. The results show that dehumidifier enthalpy pinch is dominating the performance. Abstract: The humidification-dehumidification (HDH) desalination is a favorable option for small scale and off-grid applications. Its main disadvantage is the low thermal efficiency compared with other thermal desalination techniques. This study demonstrates the importance of using the thermodynamic balancing concept in enhancing the thermal efficiency of HDH systems. An experimental HDH setup has been built to produce 276 kg of pure water per day (peak capacity) costing 0.033 $/L. The physical understanding of the balancing concept is clarified by representing the experimental results on the temperature enthalpy diagram. The enthalpy pinch model can be solved numerically, analytically, or pseudo-analytically to estimate the performance at the balanced conditions (upper limit of performance). Moreover, a novel parameter, dimensionless enthalpy pinch ( Ψ ¯ ) is proposed to be a measure of the thermal efficiency and a size index. The theoretical model has been validated against the experimental results with a maximum error of 6%. It can be concluded that adjusting the operating conditions to balance the system thermodynamically can improve economic performance by about 40%. Moreover, theoretically, the parametric study shows that the dehumidifier Ψ ¯ is more dominating on the gain output ratio (GOR) than the humidifier Ψ ¯ . Also, at a fixed Ψ ¯, the maximum ( T max ) and minimum ( T min ) temperature influences the GOR significantly only at a low enthalpy pinch value ( Ψ ¯  < 20% ) where decreasing T max or increasing T min has a positive effect on the GOR.